2016
DOI: 10.1016/j.mri.2016.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Segmented diffusion-weighted imaging of the prostate: Application to transperineal in-bore 3T MR image-guided targeted biopsy

Abstract: Objective-To evaluate the applicability of using single-shot and multi-shot segmented diffusion-weighted imaging (DWI) techniques to support biopsy target localization in a cohort of targeted MRI-guided prostate biopsy patients.Materials and Methods-Single-shot echo-planar diffusion-weighted imaging (SS-DWI) and multi-shot segmented (MS-DWI) were performed intra-procedurally on a 3 Tesla system in a total of 35 men, who underwent in-bore prostate biopsy inside the scanner bore. Comparisons between SS-DWI and M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 27 publications
(32 reference statements)
1
6
0
Order By: Relevance
“…From our results, quantitative diffusion measurements obtained from recently developed reduced-distortion pulse sequences (rFOV and msEPI) were in good agreement with the standard ssEPI-based measurements. In combination with the reduced distortion provided by these novel pulse sequences (as has been demonstrated in previous works [1820, 3539] as well as in this study), these results demonstrate the potential of rFOV and msEPI, at the cost of FOV size or scan time, to provide reproducible quantitative diffusion measurements compared to ssEPI. This potential may have significant research and clinical implications for diffusion MRI of the prostate.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…From our results, quantitative diffusion measurements obtained from recently developed reduced-distortion pulse sequences (rFOV and msEPI) were in good agreement with the standard ssEPI-based measurements. In combination with the reduced distortion provided by these novel pulse sequences (as has been demonstrated in previous works [1820, 3539] as well as in this study), these results demonstrate the potential of rFOV and msEPI, at the cost of FOV size or scan time, to provide reproducible quantitative diffusion measurements compared to ssEPI. This potential may have significant research and clinical implications for diffusion MRI of the prostate.…”
Section: Discussionsupporting
confidence: 86%
“…Importantly, both rFOV and msEPI enable DWI imaging with higher resolution and higher overall image quality including greater resolvable spatial resolution and reduced distortions [14, 17]. In recent studies, both rFOV and msEPI have been shown to provide improved diffusion-weighted image quality for prostate cancer detection compared to conventional ssEPI [1820, 3539].…”
Section: Introductionmentioning
confidence: 99%
“…Cardiac triggering has been explored in the upper abdomen [ 24 ]. Anti-peristaltic agents reduce image blur arising from peristaltic motion in abdominal and pelvic DW-MRI and multishot techniques may offer some advantages over single-shot techniques in reducing distortion from air within bowel [ 25 ].
Fig.
…”
Section: Data Acquisitionmentioning
confidence: 99%
“…Diffusion images provide the most critical information for cancer diagnosis in a multiparametric prostate exam, yet conventional diffusion image quality in comparison to typical T 1 and T 2 -weighted images is clearly inferior. Therefore, perfecting geometric fidelity and spatial resolution of the diffusion scan promises to be of great diagnostic value, but also very desirable for more accurate biopsy and intervention guidance (15,36). The present study demonstrates that a segmented acquisition can improve geometric fidelity and at the same time enhance spatial resolution of the diffusion imaging sequence in a multiparametric prostate exam.…”
Section: Discussionmentioning
confidence: 64%
“…With multi-coil acquisitions, parallel imaging is typically the first choice to reduce distortion artifacts (8). For greater reductions, parallel imaging can be combined with the reversed gradient method (9,10), or with segmentation along either the readout (11,12) or phase encode (13) direction, and such combinations of methods have been applied to prostate diffusion imaging (14)(15)(16)(17). An increase by a few-fold in scan time and the need for correction of motion-related phase errors are the primary downsides of segmented diffusion imaging.…”
Section: Introductionmentioning
confidence: 99%